Profil Profil 100 Publikasi Teratas yang Dikutip dalam Pendidikan STEM selama Dua Puluh Tahun Terakhir - Rizki, Iqbal Ainur (JPPS (Jurnal Penelitian Pendidikan Sains), 2022)
The research analyzes the top 100 cited publications in STEM education in the last twenty years. The research objectives are to analyze the publication type, year, sources publishing, authorship pattern, institution, country, and keywords pattern and review these top-cited publications using bibliometric analysis. The metadata used in this research is the Scopus database. The study result shows that among these top 100 publications, the most common type of publication is journal articles. Most of these publications were conducted at four-year intervals from 2014 to 2017, with an average citation per paper of 70.75. Belland is recognized as the most productive author, whereas National Research Council has become the institution with the most citations. The most contributed institutions included Purdue University and the University of Minnesota. The USA has led over highly cited publications, followed by Australia and the Netherlands. The research areas in these papers mainly emphasize education, STEM, STEM education, engineering education, and every stem aspect. The review result focus on research on the conceptual framework of STEM integration, STEM-based learning media, challenges to STEM, perspectives on STEM education, and the impact of Covid-19 on STEM education. This research implies finding research novelties about STEM education through the results of mapping and visualization patterns based on keywords that often appear.